2022
DOI: 10.1021/acs.nanolett.2c03743
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Emitters in Hexagonal Boron Nitride

Abstract: Hexagonal boron nitride (hBN) has emerged as a fascinating platform to explore quantum emitters and their applications. Beyond being a wide-bandgap material, it is also a van der Waals crystal, enabling direct exfoliation of atomically thin layers�a combination which offers unique advantages over bulk, 3D crystals. In this Mini Review we discuss the unique properties of hBN quantum emitters and highlight progress toward their future implementation in practical devices. We focus on engineering and integration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 94 publications
2
34
0
Order By: Relevance
“…Measured P SAT values of other blue emitters are 1.50 mW for F2E1, 2.10 mW for F2E4, 2.40 mW for F2E5, 6.50 mW for F2E8, and 8.90 mW for F2E9. Thus, examined emitters have P SAT ranging from 1.50 mW to 8.90 mW, similar to previously reported for blue emitters in hBN [14,15] at RT, which are slightly above typical saturation values for the visible (∼2 eV) emitters in hBN [5]. Such relatively high P SAT could be attributed to absorption cross-section of blue emitters from 405 nm excitation.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Measured P SAT values of other blue emitters are 1.50 mW for F2E1, 2.10 mW for F2E4, 2.40 mW for F2E5, 6.50 mW for F2E8, and 8.90 mW for F2E9. Thus, examined emitters have P SAT ranging from 1.50 mW to 8.90 mW, similar to previously reported for blue emitters in hBN [14,15] at RT, which are slightly above typical saturation values for the visible (∼2 eV) emitters in hBN [5]. Such relatively high P SAT could be attributed to absorption cross-section of blue emitters from 405 nm excitation.…”
Section: Introductionsupporting
confidence: 87%
“…Single photon emitters (SPEs) are widely acknowledged as key enablers to establish and deploy quantum communication and computing, which involves on-demand generation of high purity single photon emission [1][2][3] . Hexagonal boron nitride (hBN) has gained attention due to its unique properties of wide layer-dependent bandgap centred around 6 eV, high exciton binding energies, presence of optically active spin-defects and capability to host roomtemperature (RT) bright SPEs [4][5][6][7][8][9][10][11] . hBN is also attracting attention for its use as an emerging optoelectronic material for the deep ultraviolet range 12 .…”
Section: Introductionmentioning
confidence: 99%
“…(c) Upper panel: experimentally measured hBN ZPL energies generated using various techniques including nanoindentation, plasma treatment, fs laser ablation, neutron, electron, and ion irradiation methods. The emission ranges have been extracted from two comprehensive review papers, , and their occurrence is shown by the intensity of the shaded region. Lower panel: the excitation and emission spectra for various types of fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting these optical probes requires a better understanding of their spectral variability and, linked to this, the reproducible engineering and tuning of defect structures, since it is the defect crystal structure and composition (impurities, substitutional atoms, vacancies, and vacancy complexes) that dictate the photophysical properties and, by extension, the operation as a FRET probe. The top panel in Figure c shows the experimental zero phonon line (ZPL) energies of hBN optical emitters generated using various nanofabrication techniques. , The lower panel shows the excitation and emission spectra of well-known fluorophores (GFP, AF488, Cy3, Cy3.5, Cy5, AF647), demonstrating their spectral compatibility as fluorescent labels for smFRET studies with several types of hBN emitters. This optical approach to single-molecule fingerprinting also relies on strategies to control the speed of (reversible) translocations in solid-state nanopores, which could include integration with optical, optoelectronic, magnetic, or acoustic tweezers. , …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Moreover, and perhaps one of the most appealing characteristics of hexagonal boron nitride, are its large variety of single-photon emitters. They span from the UV to the low infrared, 22,23 are tunable via strain or electric fields, [24][25][26][27] and are capable of operating at room temperature and up to 800 K. 28 Experimental works over the past three years [29][30][31] have demonstrated optically detected magnetic resonance in negatively charged boron vacancy defects (V − B ), together with coherent control of the spins. 32,33 A recent study on these vacancies has shown control at room temperature of a protected qubit basis, with a coherence time as high as 0.8 µs.…”
mentioning
confidence: 99%